Bite marks on the frill of a juvenile Centrosaurus from the Late Cretaceous Dinosaur Provincial Park Formation, Alberta, Canada - David W.E. Hone; Darren H. Tanke; Caleb M. Brown (PeerJ, 2018)
Bite marks on bones can provide critical information about interactions between carnivores and animals they consumed (or attempted to) in the fossil record. Data from such interactions is somewhat sparse and is hampered by a lack of records in the scientific literature. Here, we present a rare instance of feeding traces on the frill of a juvenile ceratopsian dinosaur from the late Campanian Dinosaur Park Formation of Alberta. It is difficult to determine the likely tracemaker(s) but the strongest candidate is a small-bodied theropod such as a dromaeosaur or juvenile tyrannosaur. This marks the first documented case of carnivore consumption of a juvenile ceratopsid, but may represent scavenging as opposed to predation.